Genetic architecture, heterosis and inbreeding depression for yield and yield associated physiological traits in rice (Oryza sativa L.) under drought condition (SAARC Journal of Agriculture, 2015)
Simple and joint scaling tests led to similar inferences in respect of presence or absence of epistasis in majority of cases across the fourteen characters of six crosses in two conditions. The generation mean analysis revealed importance of additive (d) and/or dominance (h) gene effects as well as one or more of the epistatic gene interactions (i, j, l) for all the seven characters in most of the crosses under both the conditions. However, nature and magnitude of gene effects and epistatic interactions for a character exhibited considerable variation across the six crosses and two environmental conditions. Significance of dominance gene effects and epistatic interactions for most of the traits in six crosses under two conditions indicated that exploitation of heterosis through hybrid varieties appears to be a potential alternative. Only in drought condition, considerable number of crosses exhibited positive and significant estimates of standard heterosis across seven characters. Present study indicated apparent lack of desirable heterosis of requisite degree. It appears that extremely diverse nature of parents involved in six cross combinations may have resulted in incompatible gene combinations or genetic architecture in crosses resulting into poor performance and lack of heterosis for most of the characters. The positive and significant heterobeltiosis was noted for relative water content and membrane thermo stability in cross VI in irrigated condition.SAARC J. Agri., 13(1): 50-62 (2015)